TANGGUNG GUGAT INVESTOR REKSADANA TERHADAP INFORMASI SUSPENSI PT. BIBIT ATAS PRODUK REKSADANA PT. SINARMAS ASSET MANAGEMENT - Ruroh, Siti Mas (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2023)
Law No. 8 of 1995 on Capital Market regulates the obligation of public company issuers and other parties to apply the principle of openness. Article 1 number 25 of Law No. 8 of 1995 on Capital Market explains that